Une société montagnarde à l’épreuve des inondations : entre vulnérabilité et stratégies d’adaptation - Dominique Baud (VertigO)
In the Alps from the 18th century to the present day, flood variability (frequency, intensity) has led to specific practices and modes of organization on the part of society in order to guard against risk. In this sense, avoidance or adaptation strategies have been developed by mountain communities to reduce their vulnerability and potential damage. Historical archives document the impacts (damage or destruction of infrastructures, victims, destroyed roads, engraved fields, etc.) over the last centuries and make it possible to understand the efficiency of past risk management methods. This article focuses on the evolution of vulnerability / exposure and management methods (protection arrangements, etc.) based on the study of cartographic documents (old cadastres) and textual documents (testimonies, expert reports, quantification of the damage, etc.) of a mountain territory. The objective is to provide a basis for reflection to understand how a territory heavily impacted over a given period of time manages its propensity of damages subsequently. Through the study of “Aime” in the Tarentaise valley (Savoie), we will see whether three high-impact flood events in the 18th century (1732, 1733 and 1778) changed permanently or not the land use and the practices of the inhabitants. The use of flood reports, Sardinian cadaster (1730) and French cadaster (1890) will allow spatialization of the damage caused by floods and changes in land use between the beginning of the 18th century and the end of the 19th century.